Biological and therapeutic effects of honey produced by honey bees and stingless bees: a comparative review - Pasupuleti Visweswara Rao; Kumara Thevan Krishnan; Naguib Salleh; Siew Hua Gan
Honey is a natural product produced by both honey bees and stingless bees. Both types of honey containunique and distinct types of phenolic and flavonoid compounds of variable biological and clinical impor-tance. Honey is one of the most effective natural products used for wound healing. In this review, thetraditional uses and clinical applications of both honey bee and stingless bee honey – such as antimicro-bial, antioxidant, anti-inflammatory, anticancer, antihyperlipidemic, and cardioprotective properties; thetreatment of eye disorders, gastrointestinal tract diseases, neurological disorders, and fertility disordersand wound healing activity are described.